Ethnic differences in oral health and use of dental services: cross-sectional study using the 2009 Adult Dental Health Survey. Issue 1 (December 2017) - Arora, Garima; Mackay, Daniel; Conway, David; Pell, Jill
Abstract Background Oral health impacts on general health and quality of life, and oral diseases are the most common non-communicable diseases worldwide. Non-White ethnic groups account for an increasing proportion of the UK population. This study explores whether there are ethnic differences in oral health and whether these are explained by differences in sociodemographic or lifestyle factors, or use of dental services. Methods We used the Adult Dental Health Survey 2009 to conduct a cross-sectional study of the adult general population in England, Wales and Northern Ireland. Ethnic groups were compared in terms of oral health, lifestyle and use of dental services. Logistic regression analyses were used to determine whether ethnic differences in fillings, extractions and missing teeth persisted after adjustment for potential sociodemographic confounders and whether they were explained by lifestyle or dental service mediators. Results The study comprised 10, 435 (94.6 %) White, 272 (2.5 %) Indian, 165 (1.5 %) Pakistani/Bangladeshi and 187 (1.7 %) Black participants. After adjusting for confounders, South Asian participants were significantly less likely, than White, to have fillings (Indian adjusted OR 0.25, 95 % CI 0.17-0.37; Pakistani/Bangladeshi adjusted OR 0.43, 95 % CI 0.26-0.69), dental extractions (Indian adjusted OR 0.33, 95 % CI 0.23-0.47; Pakistani/Bangladeshi adjusted OR 0.41, 95 % CI 0.26-0.63), and <20 teeth (Indian adjusted OR 0.31, 95 % CI 0.16-0.59; Pakistani/Bangladeshi adjusted OR 0.22, 95 % CI 0.08-0.57). They attended the dentist less frequently and were more likely to add sugar to hot drinks, but were significantly less likely to consume sweets and cakes. Adjustment for these attenuated the differences but they remained significant. Black participants had reduced risk of all outcomes but after adjustment for lifestyle the difference in fillings was attenuated, and extractions and tooth loss became non-significant. Conclusions Contrary to most health inequalities, oral health was better among non-White groups, in spite of lower use of dental services. The differences could be partially explained by reported differences in dietary sugar.